Lena Jonson and Andrei Erofeev (eds.): Russia – Art Resistance and the Conservative-Authoritarian Zeitgeist - Sylvia Chassaing (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2020)
Sylvia Chassaing’s review of  Russia – Art Resistance and the Conservative-Authoritarian Zeitgeist, edited by Lena Jonson and Andrei Erofeev (2018).